Snow - Shulevitz, Uri, 1935- (New York : Farrar Straus Giroux, 1998)
As snowflakes slowly come down, one by one, people in the city ignore them, and only a boy and his dog think that the snowfall will amount to anything
Keywords: Snow -- Juvenile fiction; City and town life -- Juvenile fiction; Caldecott Honor book; City and town life -- Fiction; Snow -- Fiction; Picture books